Vocal activity rate index: a useful method to infer terrestrial bird abundance with acoustic monitoring. (3rd April 2019) - Pérez‐Granados, Cristian; Bota, Gerard; Giralt, David; Barrero, Adrián; Gómez‐Catasús, Julia; Bustillo‐De La Rosa, Daniel; Traba, Juan
Abstract : Autonomous recording units have been widely used in a large number of bird studies in recent years, but challenges remain in estimating abundance based on acoustic monitoring. We tested whether vocal activity rate index (VAR; the number of songs per unit time for a species), recorded using autonomous recording units, was related to population abundance in two terrestrial bird species, the European Bee‐eater Merops apiaster and the Dupont's Lark Chersophilus duponti . We took recordings at sites where censuses were also carried out to estimate local populations around recorders. We found a positive and significant relationship for the two monitored species. Although our results are not conclusive, the strong and significant relationship found for both monitored species suggests that VAR may be used to infer bird abundance around recorders in terrestrial species. We describe five logical steps for using the VAR with autonomous recording units in other species to guide future studies.